Circulating microRNA biomarkers in melanoma and non-melanoma skin cancer. (4th March 2022) - Durante, Giorgio; Broseghini, Elisabetta; Comito, Francesca; Naddeo, Maria; Milani, Massimo; Salamon, Irene; Campione, Elena; Dika, Emi; Ferracin, Manuela
ABSTRACT: Introduction: Skin cancer is the most common type of cancer and is classified in melanoma and non-melanoma cancers, which include basal cell, squamous cell, and Merkel cell carcinoma. Specific microRNAs are dysregulated in each skin cancer type. MicroRNAs act as oncogene or tumor suppressor gene regulators and are actively released from tumor cells in the circulation. Cell-free microRNAs serve many, and possibly yet unexplored, functional roles, but their presence and abundance in the blood has been investigated as disease biomarker. Indeed, specific microRNAs can be isolated and quantified in the blood, usually in serum or plasma fractions, where they are uncommonly stable. MicroRNA levels reflect underlying conditions and have been associated with skin cancer presence, stage, evolution, or therapy efficacy. Areas covered: In this review, we summarize the state of the art on circulating microRNAs detectable in skin cancer patients including all the studies that performed microRNA identification and quantification in the circulation using appropriate sample size and statistics and providing detailed methodology, with a specific focus on diagnostic and prognostic biomarkers. Expert Opinion: Circulating microRNAs display a relevant biomarker potential. We expect the development of methodological guidelines and standardized protocols for circulating miRNA quantification in clinical settings.